Non-Preference for Oviposition Cassava Lace Bug Vatiga illudens (Hemiptera: Tingidae) by Cassava Cultivars (2016)
The aim of this study was to evaluate the non-preference for oviposition Vatiga illudens (Drake, 1922) (Hemiptera: Tingidae) in cassava cultivars. The following cultivars were compared: Kiriris, N-25, Fécula Branca, IAC 90, M Ecu 72 and IAC 576, preference tests for oviposition were conducted, with a choice test in semi-field conditions. An adult double V. illudens was released in the leaves of cassava of their cultivars. Allowed to feeding and oviposition of these insects for 72 hours. We evaluated the number of eggs / female / leaf, the number of droppings / couple / sheet and the preference index for oviposition. The cultivar M Ecu 72 demonstrated to be highly resistant to cassava lace bug. This study showed that there are resistance mechanisms to V. illudens in cassava cultivars, which justifies the new studies on these cultivars in breeding programs, aiming to control this pest and identification of such mechanisms.